Symptomatic relapse of HIV-associated cryptococcal meningitis: recurrent cryptococcal meningitis or Cryptococcus-related immune reconstitution inflammatory syndrome?. (April 2014) - Jhamb, Rajat; Kashyap, Bineeta; Das, Shukla; Berry, Neha; Garg, Arun
Cryptococcosis, a significant opportunistic infection, has become a global concern since the advent of immunosuppressive chemotherapy or in immunodeficient patients. Host responses range from a harmless colonization to disseminated disease. An accurate or definitive diagnosis in patients with cryptococcal meningitis is often delayed because of the similar clinical presentation and biochemical or cerebrospinal fluid findings to those of a variety of infectious and non-infectious aetiologies, most of which are also especially prevalent in developing countries. Rarely, patients with cryptococcal meningitis can develop immune reconstitution inflammatory syndrome (IRIS) when initiated on combination antiretroviral therapy (cART) the diagnosis which is often missed and can be fatal. Due to the similar presentation of infection and IRIS, it is often confused with the relapse of cryptococcal meningitis. We report a case of paradoxical recurrent meningitis in response to the initiation of cART in a patient diagnosed with cryptococcal meningitis and propose that the recurrent symptoms resulted from a therapy-induced reconstitution of the immune response against residual Cryptococcus neoformans.